Some of the Corruptogenic Factors of Environmental Legislation in the Russian Federation - Navasardova, Eleonora Sergeevna; Klyukovskaya, Irina Nikolaevna; Galstyan, Inessa Shagenovna; Kolesnikova, Kira Vladimirovna; Nutrikhin, Roman Vladimirovich (International Journal of Economics and Financial Issues, 2015)
The article investigates some of the shortcomings of environmental legislation, which lead to loss of valuable ecological systems in practice. The article examines two groups of regulations and their practical implementation. The first of the considered groups of normative legal sources regulates land and forest relations. It revealed corruptogenic rules that now allow to bypass the law to withdraw forest lands and specially protected natural reservations from these categories and transfer them to private ownership. In practice, this leads to deforestation and development of territories that are of great nature conservation value. The second group of normative legal acts relates to the regulation of resort relations. As a result of recent changes in environmental legislation, resorts and health and recreation areas were excluded from the specially protected natural reservations and were granted the status of just "conservation areas". At the same time, the criminal and administrative legislation has not changed. As a result, the legal regime of sanitary and mountain-sanitary conservation of resorts was left without adequate criminal and administrative protection, which may lead to the loss of natural medicinal resources and encourage corrupt activity. Keywords: environmental legislation, grant of land, regional legislation, corruption JEL Classifications: Q23; Q24; Q28; R14; R52